Analisis Yuridis Perlindungan Hak Cipta terhadap Karya Sastra Berbentuk Fiksi Penggemar (Alternate Universe) pada Platform Wattpad Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Muarifah, Muarifah; Suliantoro, Adi (Wajah Hukum, 2025)
Wattpad, as a digital storytelling platform, has become increasingly popular among writers, particularly in producing derivative works known as Alternate Universe (AU) fiction. These works frequently incorporate elements from existing intellectual property, including the names, images, and personas of public figures or fictional characters, often without prior authorization. This study aims to examine the legal protection afforded by copyright law to AU literary works published on the Wattpad platform, analyze the legal consequences of publishing such works that depict identifiable figures without consent, and explore efforts to raise awareness among Wattpad authors regarding copyright compliance. The research addresses the following issues: the juridical analysis of copyright protection for AU-based literature, the legal implications of unauthorized use of celebrity identity, and strategies to promote copyright awareness among content creators on Wattpad. Employing a normative juridical method with a qualitative approach, data were collected through legal literature review and expert interviews. The findings indicate that the use of identifiable personal attributes in AU works without permission constitutes a violation of copyright law, particularly infringing upon the moral and economic rights of the original rights holders. Furthermore, a lack of legal literacy among digital authors presents a significant challenge in the enforcement of intellectual property rights. Hence, systematic education and legal oversight are essential to uphold copyright protections in the digital creative space.